Theatrical Medicine: Aboriginal Performance, Ritual and Commemoration (for Vanessa Lee Buckner) - La Flamme, Michelle (Theatre Research in Canada / Recherches théâtrales au Canada, 2010)
The paper begins by discussing some Aboriginal teachings offering the author’s working definition of Medicine based on the teachings that elders have shared. These cultural traditions reflect a belief in the power of performance and the possibility of performance as medicinal. The paper applies some of these teachings about Medicine to suggest that the form and experience of these theatrical events can be understood as contemporary good Medicine. These performances and plays by Aboriginal people bring balance to the witnesses through honouring the deceased by way of naming rituals, they bring balance to communities by showing the humanity of Aboriginal women, and they provide a cathartic ritual or ceremony for the release of trauma. Résumé Cet article commence par présenter un certain nombre d’enseignements et de cérémonies de la tradition autochtone, pour ensuite proposer une définition de la médecine fondée sur les enseignements des Anciens. Ces traditions culturelles reflètent une croyance dans le pouvoir de la performance et dans ses possibilités médicinales. L’article étudie quelques enseignements sur la médecine et décèle dans la forme et l’expérience de ces événements théâtraux des propriétés médicinales contemporaines. Les performances et les pièces d’artistes autochtones contribuent au mieux-être des témoins qui rendent hommage aux femmes décédées par une lecture rituelle de leurs noms; elles contribuent au mieux-être des communautés en montrant l’humanité des femmes autochtones et elles fournissent un rituel ou une cérémonie cathartique qui permet d’évacuer le traumatisme.